2016
DOI: 10.1136/ebmed-2016-110401
|View full text |Cite
|
Sign up to set email alerts
|

New evidence pyramid

Abstract: A pyramid has expressed the idea of hierarchy of medical evidence for so long, that not all evidence is the same. Systematic reviews and meta-analyses have been placed at the top of this pyramid for several good reasons. However, there are several counterarguments to this placement. We suggest another way of looking at the evidence-based medicine pyramid and explain how systematic reviews and meta-analyses are tools for consuming evidence—that is, appraising, synthesising and applying evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
629
1
38

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 989 publications
(723 citation statements)
references
References 11 publications
4
629
1
38
Order By: Relevance
“…Evidence from healthcare settings is supported by the prominent tool known as the evidence pyramid (Murad et al, 2016). The case control design, represented by 61% of the total eligible studies, is known to have low quality of evidence (it is found at the base of the evidence pyramid).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from healthcare settings is supported by the prominent tool known as the evidence pyramid (Murad et al, 2016). The case control design, represented by 61% of the total eligible studies, is known to have low quality of evidence (it is found at the base of the evidence pyramid).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the evidence-based medicine approach, various "hierarchy of evidence" stratifications have also emerged [1][2][3] . Overall, those stratifications attempt to characterize underlying bias (that is, validity) and emphasize the relative quality of different forms of evidence.…”
Section: Evidence In Medicine: Math Versus Biology!mentioning
confidence: 99%
“…Overall, those stratifications attempt to characterize underlying bias (that is, validity) and emphasize the relative quality of different forms of evidence. In a traditional pyramidal representation ( Figure 1) 2,3 , systematic reviews and meta-analyses of randomized clinical trials (rcts) represent the pinnacle of the pyramid, followed by individual rcts and observational studies (for example, case-control or cohort studies). Conversely, case reports and series, often called "anecdotal evidence," are placed at the bottom of the pyramid.…”
Section: Evidence In Medicine: Math Versus Biology!mentioning
confidence: 99%
“…With this in mind, I found the ‘New Evidence Pyramid’ proposed by Murad et al 3 to be ingenious. It is graphically simple while conveying that quality varies in primary studies, and that there are inherent difficulties in fully relying on systematic reviews and meta-analysis without understanding the strength of the primary evidence and the methodology of the analyses.…”
mentioning
confidence: 93%